2016
DOI: 10.1126/science.aab2116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct routes of lineage development reshape the human blood hierarchy across ontogeny

Abstract: Classically, blood arises from stem cells through a series of oligopotent progenitors that become increasingly restricted to unipotent progenitors, each slotted into a hierarchical layer based on their differentiation potential. The presence of oligopotent cells is critical to the standard model of blood differentiation as they define the path from stem cells to unipotent progenitors. We developed a new cell-sorting scheme to resolve myeloid (My), erythroid (Er) and megakaryocytic (Mk) fates from single CD34+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
674
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(781 citation statements)
references
References 48 publications
74
674
1
4
Order By: Relevance
“…The small branch cell counts (37-380) precluded recursive application of TreeTop (Supp Fig 13, Online Methods). The results from TreeTop are therefore consistent with recent findings in favour of a flat hierarchy [5][6][7] .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The small branch cell counts (37-380) precluded recursive application of TreeTop (Supp Fig 13, Online Methods). The results from TreeTop are therefore consistent with recent findings in favour of a flat hierarchy [5][6][7] .…”
supporting
confidence: 82%
“…Each sample of the datasets described above was generated from an n-dimensional space, where n was uniformly sampled from [6,30]. Of these, we found that the distributions of branching scores observed for triangular data were higher than the other topologies considered by a considerable margin (Supp Figs 1-2).…”
Section: Assessment Of Branch Point Significancementioning
confidence: 99%
“…Prenatally, oligopotent progenitor cells residing in the fetal liver give rise to myeloid, erythroid, and megakaryocyte fates. Multipotent or unipotent progenitor classes predominate in the bone marrow, giving rise to the adult megakaryocyte and erythroid classes 14. Interestingly it has been recently shown that the murine lung is a reservoir for hematopoietic progenitors and megakaryocytes, and a site for platelet biogenesis,15 although the significance of these findings in human megakaryopoiesis is still unknown.…”
Section: Genetic Regulation Of Normal Megakaryopoiesismentioning
confidence: 99%
“…Nota et al [15] deined the MPPs that were CD90 − CD49f − as transiently engrafting cells (2-4 weeks in NSG mice) or short-term repopulating HSCs and concluded that most HSCs reside in the CD90+ fraction, but 1 in 5.5 UCB HSCs lacked CD90 expression, and approximately 10% of the UCB CD90+CD49f+ cells fraction are HSCs [15]. More recent experiments from Nota et al [86] have added further to our understanding of the human hematopoietic lineage and the developmental changes it undergoes from fetal liver to UCB to bone marrow hematopoiesis. Importantly, these investigators developed an in vitro single-cell assay that exclusively assesses myeloid, including erythroid and megakaryocytic, lineage potential of individual CD34+ cells by combining MS-5 stromal cultures with LDL and eight cytokines, stem cell factor, thrombopoietin, FMS-like tyrosine kinase 3 ligand, interleukin 6, interleukin 3, interleukin 11, granulocyte macrophage colony stimulating factor and erythropoietin (SCF, TPO, Flt3L, IL6, IL3, IL11, GM-CSF and Epo respectively) and found that 2% of the enriched UCB CD49f+ HSCs gave rise to such clones [86].…”
Section: Other Uses Of Ucbmentioning
confidence: 99%
“…More recent experiments from Nota et al [86] have added further to our understanding of the human hematopoietic lineage and the developmental changes it undergoes from fetal liver to UCB to bone marrow hematopoiesis. Importantly, these investigators developed an in vitro single-cell assay that exclusively assesses myeloid, including erythroid and megakaryocytic, lineage potential of individual CD34+ cells by combining MS-5 stromal cultures with LDL and eight cytokines, stem cell factor, thrombopoietin, FMS-like tyrosine kinase 3 ligand, interleukin 6, interleukin 3, interleukin 11, granulocyte macrophage colony stimulating factor and erythropoietin (SCF, TPO, Flt3L, IL6, IL3, IL11, GM-CSF and Epo respectively) and found that 2% of the enriched UCB CD49f+ HSCs gave rise to such clones [86]. Of these, approximately half formed high proliferative potential (HPP)-CFU [86].…”
Section: Other Uses Of Ucbmentioning
confidence: 99%